Bodies of cunicularity in supersonic flow - Myburgh, Sabrina Gabrielle (University of the Witwatersrand, Johannesburg, 2024)
Prior studies outlined the success of using randomised High Porosity Cellular Material cyl- inders both numerically and experimentally, however showed limited applicability to real-life aerodynamics applications. The primary effect of supersonic flow over porous media is to attenuate the bow wave by reducing the angle of incidence and redistributing the flow field, significantly reducing wave drag. The aim of this work was to investigate the drag-reduction effect of organised porosity within conic bodies of revolution on the supersonic flow field. Various organised porous cone-cylinders were developed to investigate the effect of the porous structure on the flow field, including shock waves, momentum changes and flow structures in and around the por- ous body. Several conic profiles were investigated. A numerical and experimental investigation was carried out in steady, supersonic flow at Mach 3.5 (Re = 3.9 × 10−5). The conic models had a porosity of ≈ 60%. The blow down supersonic wind tunnel facility at the University of the Witwatersrand was used for the exper- imentation, where schlieren photographs were captured along with drag force measurements of the solid and porous baseline cones. Numerical CFD simulations were carried out for a wider range of porous configurations using ANSYS Fluent R22.2. The numerical, experi- mental and literature Cd and flow visualisation were used to validate the numerical method, showing good agreement across data sets. Certain cunicular arrangements effectively reduced the drag in some shapes, while others worsened the drag. The greatest drag reduction of 40% was achieved in the cunicular BS4 Ellipsoid. The change in drag was associated with three sources, namely wave drag, jet v interaction, and momentum addition by the jet. These changes resulted from the flow inter- actions occurring within the inlet, internal and venting structures. Changes in drag depended on several factors, including vent geometry, expansion ratio, exit angle, inlet geometry and the crossflow condition, to name a few. Wave drag reduction was dependent on shock at- tenuation and reducing the wave angle, which was generally ensured by the conic surface pores absorbing energy from the bow wave. The jet interaction and momentum recovery were dependent on vent expansion ratio, exit angle and crossflow condition. The jet interaction had the greatest increase on the drag of the system, however, the effects of this were mitigated by using low vent angles with correct expansion ratios to maximise momentum recovery from the jet. The effect of the combined system was specific to the particular case, where the solid cone shape greatly influenced the overall performance. The effect on drag reduction was cumulative, sensitive and highly dependent on the individual case. The cunicular system is a viable drag reduction mechanism in conic bodies, however careful balancing of the porous inflow, outflow, bow wave and venting conditions is required in order to achieve significant drag reduction.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, In the Faculty of Engineering and the Built Environment , School of Mechanical, Industrial and Aeronautical Engineering, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Drag reduction; jet injection; supersonic flow; SDG-7: Affordable and clean energy